The Importance of Digital Modeling to Understand the Functional Change of Urban Landuses (Journal of University of Babylon for Engineering Sciences, 2018)
Mathematical modeling is one of the important tools to derive theories and indicate causal relations between spatial variability of various phenomena, scientific theory developed for the purpose of conducting spatial analysis of the phenomenon through time they used mathematical modeling to link Variables and factors influencing the phenomenon.Mathematical modeling has evolved after entering the digital technology, the wording of the various models is done by the computer via custom software designed for that purpose, geographic information systems (GIS) is one of the most important digital systems that allow researchers using mathematical modeling In the analysis and interpretation of spatial relations of various phenomena through fellowship.Urban land uses are one of spatial phenomena in cities created for various functions such as housing and shopping, transport and mobility, manufacturing, education, health and other services to the city through the relationships and interactions among them and are subject to the rules of logical theory suit City environment and administered through planning and management regulations .Urban landuses affected in Najaf during 1994 till 2018  by factors influenced the change of the relationship between them, have changed their functions have become different in nature from the planned situation, This led to problems,and Prompting the researcher to adopt digital mathematical modeling specifically )GWR) to identify causal factors of functional change in urban land uses in the city during the study period as well as try to interpret the indicators and results and representation Digital maps allow for the possibility of developing a planning and management.